Penilaian Kinerja Pegawai Negeri Sipil pada Badan Kepegawaian Daerah Provinsi Bengkulu - loly nurfianto; Fachruzzaman Fachruzzaman; Yumiati Yumiati (Journal Of Administration and Educational Management (ALIGNMENT), 2022)
Employee Performance Assessment is one of the links in staffing management. Assessment of work performance is an evaluation of the results of the implementation of an employee's work in order to achieve the objectives of an organization based on the benchmarks and standards set. Bengkulu Provincial Staffing Agency is the opd that first conducted and implemented the Assessment of Work Performance in the Bengkulu Provincial Government Environment, which refers to Government Regulation No. 46 of 2011 and Regulation of the Head of State Personnel Agency No. 1 of 2013 concerning The Implementation Provisions of Government Regulation No. 46 of 2011, which is a guideline for Officials who assess or Civil Servants in implementing the provisions of civil servant work performance assessment. This research was conducted in order to know and describe the implementation of civil servant work performance assessment, know the results of civil servant work performance assessment, and to know what are the factors that hinder the Assessment of Civil Servants' Work Performance. This study uses qualitative method based on case study, informant interview as many as 9 (nine) people. Based on the results of the study, the implementation of civil servant performance assessment that civil servants in the Regional Staffing Agency of Bengkulu Province has compiled employee work targets, and the results of the assessment of the performance of civil servants have been running well which can be seen from the results of civil servant performance targets in 2018 and 2019 that have been good value.